Rodrigo Pais Photo Archive, a Resource of Good Practices for the Religious Heritage. The Exhibition “Catholic Church and Society in Italy in the Second Half of the Twentieth Century” - Furini, Glenda; Gambetta, Guido (Almatourism - Journal of Tourism, Culture and Territorial Development, 2018)
Sometimes we underestimate the importance of linking together different cultural assets in order to implement enhancement strategies suitable to cross the sectorial borders. Instead, we tend to consider watertight compartments and run the risk to target single cultural products which could be potentially offered to a wider audience. The photographic exhibition “Catholic Church and Society in the Second Half of the Twentieth Century” aimed, ever since its beginning, to cross these borders with a thematic selection of shots taken by photographer Rodrigo Pais, on display in the hall of the former oratory of the Basilica of San Martino Maggiore. The building is currently in a poor conservation status, although its originary splendor is still visible in both the architectural structure and decoration elements, featuring a large fresco dating back to the 17th century entirely covering one of the four walls of the hall. This place requires a proper visibility in order to regain its vitality and be able to foster once again cultural exchanges.